AHMET ERDEM TOZOĞLU, “DEMİRYOLU VE KENT 19. YÜZYILDA OSMANLI BALKAN ŞEHİRLERİNİN MEKÂNSAL DEĞİŞİMİ”,Türkiye İş Bankası Kültür Yayınları, İstanbul, 2024, XII+352 PAGES, ISBN: 9786254299599. - Anıl Göç (Journal of Balkan Studies)
Ahmet Erdem Tozoğlu’s book, Demiryolu ve Kent (Railway and City), originates from his 2013 doctoral dissertation, which was written in English at Middle East Technical University. The author developed the research over nearly 10 years before its Turkish publication. It makes the book an adaptation rather than a translation of the dissertation.